How oxygen uptake, ground reaction forces, and kinematics respond to air resistance and drafting during treadmill running - Steele, J. R.; VanKeersbilck, L.; Bruening, D.; Gifford, J.; Seeley, M.; Hunter, I. (Journal of Applied Biomechanics, 2025)
This study investigated the effects of air resistance and drafting on oxygen uptake, ground reaction forces, and lower body kinematics during treadmill running. Thirty-three trained distance runners ran at 3.35 to 4.29 m/s (80%-85% of critical speed) on a force-instrumented treadmill within a wind tunnel under 5 conditions: no fan (NF), normal wind, normal wind with drafting, headwind (HW), and HW with drafting. Drafting involved running 1 m behind a mannequin. Oxygen uptake increased by 4.7% in HW compared with NF (P < .001) and decreased by 2.8% in HW with drafting compared with HW (P < .001). HW increased both braking and propulsive forces, accompanied by greater hip and knee flexion at initial contact, compared with NF. Drafting mitigated these effects but did not return oxygen uptake or biomechanical metrics to NF levels. Results suggest that air resistance imposes a metabolic cost, while drafting reduces but does no eliminate this cost. The most notable biomechanical adaptations occurred in horizontal ground reaction forces and lower body kinematics, indicating that both are influential in the metabolic response to air resistance. Future research should refine experimental setups to further explore air resistance`s effects on biomechanics and energy cost.